2018
DOI: 10.1002/jbio.201800019
|View full text |Cite
|
Sign up to set email alerts
|

In vivo metabolic imaging and monitoring of brown and beige fat

Abstract: Activation of the thermogenic brown and beige fat is an effective means to increasing whole-body energy expenditure. In this work, a unique label-free method was developed to quantitatively assess the metabolism and thermogenesis of mouse adipose tissues in vivo. Specifically, an optical redox ratio (ORR) based on the endogenous fluorescence of mitochondrial metabolic coenzymes (nicotinamide adenine dinucleotide and flavin adenine dinucleotide) was used to measure the metabolic state of adipocytes. Our finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 59 publications
(81 reference statements)
0
23
0
Order By: Relevance
“…Therefore, the optical redox ratio (ORR) was defined as the relative fluorescence intensity of NADH and FAD, and the oxidation-reduction ratio in mitochondria can be evaluated by the ORR using label-free fluorescence microscopy. We found that the ORR of BAT increases significantly after NE injection in mice, which is correlated with the temperature rise in BAT induced by thermogenesis [14]. In our recent work, the ORR was used to monitor the thermogenesis of BAT in vivo [14].…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Therefore, the optical redox ratio (ORR) was defined as the relative fluorescence intensity of NADH and FAD, and the oxidation-reduction ratio in mitochondria can be evaluated by the ORR using label-free fluorescence microscopy. We found that the ORR of BAT increases significantly after NE injection in mice, which is correlated with the temperature rise in BAT induced by thermogenesis [14]. In our recent work, the ORR was used to monitor the thermogenesis of BAT in vivo [14].…”
Section: Introductionmentioning
confidence: 89%
“…The SRS images and spectra suggest that the vacuoles structures in the fluorescence images of adipocytes were LDs enriched with triacylglycerol [14]. Since the lipids and cytoplasm of adipocytes have distinct fluorescence spectra [14], the lipid fluorescence can be excluded using dualchannel ratiometric image masks ( Figure S6). Since the lipids and cytoplasm of adipocytes have distinct fluorescence spectra [14], the lipid fluorescence can be excluded using dualchannel ratiometric image masks ( Figure S6).…”
Section: Analysis On Orr and Fltmentioning
confidence: 99%
See 3 more Smart Citations